The Evolution of Labor Markets - Huberman, Michael (The Routledge Handbook of Modern Economic History, 2012)
Informed by labor economics and labor history, the economic history of labor markets is an alternative and unified approach to study the wage and employment relation. This broad field encompasses the nature, organization, and conditions of work, as well as the non-wage compensation labor earned. It is an alternative approach because, unlike the economics’ textbook model, the economic historian does not perceive the labor market as static. Rather, economic history provides a framework to examine the feedback mechanisms – the dynamic relation – between labor markets and technological change, business organization, government regulation, product markets, and the preferences of participants themselves. Put differently, history provides rich examples of the many margins of adjustment in labor markets across space and time, in addition to wage and employment dimensions.